The Philippine Islands, 1493-1803 $1 (BVolume 01 of 55 :s - Blair, Emma Helen, 1851-1911; Bourne, Edward Gaylord, 1860-1908; Robertson, James Alexander, 1873-1939 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Philippine Islands, 1493-1803 $1 (BVolume 01 of 55" by Emma Helen Blair, James Alexander Robertson, and Edward Gaylord Bourne is a historical account written in the late 19th century. This comprehensive work delves into the exploration, colonization, and cultural evolution of the Philippine archipelago during its early interactions with European nations, tracing developments from the arrival of Spanish explorers to the early 16th century. At the start of this volume, the authors provide an overview of the historical context leading to the documentation of the Philippines, highlighting the Papal Bulls issued by Pope Alexander VI and the Treaty of Tordesillas that defined territorial claims. This section sets the stage for understanding the complex dynamics of colonization, cultural exchanges, and the Catholic missions that aimed to convert the islands' inhabitants. It emphasizes the importance of collecting and presenting historical documents in English, thus making this significant history accessible to scholars and the interested public. (This is an automatically generated summary.)s
Release date is 2004-08-22
Produced by Jeroen Hellingman and the Distributed Proofreaders Team
Keywords: Philippines -- History -- Sources; Missions -- Philippines; Philippines -- Discovery and exploration; Demarcation line of Alexander VI